2018
DOI: 10.13189/ujer.2018.060825
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Predictive Role of Scientific Creativity on Preservice Science Teachers' Academic Motivation

Abstract: The purpose of this research is to examine preservice science teachers' development of academic motivation and scientific creativity. It also investigated the predictive role of academic motivation on preservice science teachers' scientific creativity. The study group of the research consisted of (N=140) preservice science teachers who are studying at the Faculty of Education located in Northwest Black Sea Region of Turkey during the fall semester of the 2016-2017 academic year. Data were collected through "Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…This result could be attributed to the fact that when one is interested in a concept, the thinking capacity of that person is activated, and that gives rise to creativity. This finding collaborates with earlier studies that indicated a positive relationship between the interest and creativity of teachers (Chan and Yuen, 2014;Akkanat and Gokdere, 2015;Baka, 2018;Zaina and Matore, 2019;Akyıldız and Çelik, 2020). Creative teachers see creativity as fun and so try new things.…”
Section: Discussionsupporting
confidence: 90%
“…This result could be attributed to the fact that when one is interested in a concept, the thinking capacity of that person is activated, and that gives rise to creativity. This finding collaborates with earlier studies that indicated a positive relationship between the interest and creativity of teachers (Chan and Yuen, 2014;Akkanat and Gokdere, 2015;Baka, 2018;Zaina and Matore, 2019;Akyıldız and Çelik, 2020). Creative teachers see creativity as fun and so try new things.…”
Section: Discussionsupporting
confidence: 90%
“…Structuring and solving problems encountered is a process of creativity. Therefore, individuals who can use scientific process skills in the problem-solving process are considered to have more scientific creativity (Bakac, 2018;Hu & Adey, 2002;Mumford, Reiter-Palmon, & Redmond, 1994). The fact that scientific process skills, problem-solving skills, and scientific creativity are related to each other in the science course (Aktamis & Ergin, 2007;Cheng, 2004) shows that science education and scientific creativity have a common point (Liang, 2002).…”
Section: Introductionmentioning
confidence: 99%